2009
DOI: 10.1634/theoncologist.2008-0227
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Hypocalcemia and Serum Creatinine Increase in Patients with Bone Metastases Treated with Zoledronic Acid

Abstract: Background. Zoledronic acid belongs to the new generation of bisphosphonates with demonstrated clinical benefit for the treatment of bone metastases from different kinds of neoplasms. Hypocalcemia and serum creatinine elevation are expected adverse events during this therapy. The monitoring of serum calcium and creatinine is therefore recommended. The primary aim of this study was to establish the actual incidence of hypocalcemia and serum creatinine elevation during treatment with zoledronic acid. Skeletal-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…All of the patients were asymptomatic to the hypocalcemia; although they claimed to have complied withv regular use of Ca and vitamin D supplements. Similarly, Chennuru et al and Zuradelli et al reported hypocalcemia after zoledronic acid infusion to a heterogenous group of cancer patients (prostate carcinoma, breast cancer, multiple myeloma, and lung cancer) (13,14) . To the best of our knowledge, this is the first study documenting asymptomatic but statistically significant decrease in serum Ca levels in postmenopausal osteoporosis.…”
Section: Discussionmentioning
confidence: 87%
“…All of the patients were asymptomatic to the hypocalcemia; although they claimed to have complied withv regular use of Ca and vitamin D supplements. Similarly, Chennuru et al and Zuradelli et al reported hypocalcemia after zoledronic acid infusion to a heterogenous group of cancer patients (prostate carcinoma, breast cancer, multiple myeloma, and lung cancer) (13,14) . To the best of our knowledge, this is the first study documenting asymptomatic but statistically significant decrease in serum Ca levels in postmenopausal osteoporosis.…”
Section: Discussionmentioning
confidence: 87%
“…Chennuru and colleagues 138 reported an incidence of 8.3% over 2 years in patients prescribed zoledronic acid. Zuradelli and colleagues 161 reported an incidence of 4.6% in patients prescribed zoledronic acid (time at risk not reported).…”
Section: Hypocalcaemiamentioning
confidence: 98%
“…ZA treatment was shown to decrease DTCs population in early breast cancer patients, indicating its potential role in combating tumor dormancy and late relapse (Aft et al 2010;Rack et al 2010). The main side effects of ZA are renal toxicity, hypocalcemia (Zuradelli et al 2009) and osteonecrosis of the jaw (Fehm et al 2009;Kyrgidis et al 2008).…”
Section: Bisphosphonatesmentioning
confidence: 99%